2012
DOI: 10.1097/sla.0b013e31827324ba
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Clinical Trial of Primary Anastomosis or Hartmann's Procedure for Perforated Left Colonic Diverticulitis With Purulent or Fecal Peritonitis

Abstract: This is the first randomized clinical trial favoring PA with diverting ileostomy over HP in patients with perforated diverticulitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(271 citation statements)
references
References 40 publications
11
251
0
9
Order By: Relevance
“…All RCTs with a proper study design according to the CONSORT guidelines were identified by a systematic literature search in peer-reviewed high impact journals in the last 3 years (2011-2013) [12][13][14][15] (Supplemental Digital Content 1: flow diagram, available at http://links.lww.com/SLA/A658). After contacting several centers in general, cardiac, and plastic surgery, we were granted full access to primary data and each patient record of 3 European trials [9][10][11] addressing different surgical interventions and diseases in compliance with our study design. The first trial focused on the rate of pancreatic fistulas after pancreaticoduodenectomy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All RCTs with a proper study design according to the CONSORT guidelines were identified by a systematic literature search in peer-reviewed high impact journals in the last 3 years (2011-2013) [12][13][14][15] (Supplemental Digital Content 1: flow diagram, available at http://links.lww.com/SLA/A658). After contacting several centers in general, cardiac, and plastic surgery, we were granted full access to primary data and each patient record of 3 European trials [9][10][11] addressing different surgical interventions and diseases in compliance with our study design. The first trial focused on the rate of pancreatic fistulas after pancreaticoduodenectomy.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Each postoperative event in each patient was assessed on site and graded according to the Clavien-Dindo classification, which is based on the treatment used to correct the postoperative complication. 3 For the development of the CCI, we used the established Clavien-Dindo classification system 3 for complications, adopting methods from operation-risk-index analysis in marketing research and developed a formula that considers any combination of complications.…”
Section: Data Collection and Primary Endpointmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the first randomized trial comparing Hartmann's procedure and primary anastomosis with diverting ileostomy for perforated diverticulitis with purulent or faecal peritonitis was published [43]. The trial reported no differences between the groups with regard to overall complications and morbidity and mortality for the initial colon resection, but the Hartmann's group had a significantly lower stoma reversal rate and significantly higher rates of serious complications following the reversal surgery.…”
Section: Primary Anastomosis Versus Hartmann's Proceduresmentioning
confidence: 99%
“…71,72 The first randomised trial of Hartmann's procedure vs. primary anastomosis with a covering ileosotomy in patients with Hinchey III/IV disease reported no difference in initial mortality, but a reduction in length of stay, lower costs, fewer serious complications and greater stoma reversal rates in the primary anastomosis group. 73 The trial was stopped due to a low accrual rate and significant outcomes being shown in secondary endpoints. Recently, patients with generalised peritonitis with Hinchey grade I-III disease (Table 3) on CT scan have been managed with laparoscopic washout and drain placement with promising results reported from prospective and retrospective studies.…”
Section: Conservative/medicalmentioning
confidence: 99%